PENERAPAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS VI DI SDN 1 SUKAHURIP - Karim, Yusup Abdul; Hidayat, Yusuf; Purbayani, Rini (Jurnal Intisabi, 2025)
Critical thinking is a crucial 21st-century skill, especially for helping students solve problems and make sound decisions. This research aimed to explore the implementation of the Pancasila Student Profile Reinforcement Project (P5) in enhancing the critical thinking skills of sixth-grade students at SDN 1 Sukahurip. The P5 project proved effective in boosting the critical thinking skills of these students. This qualitative classroom action research, which adopted Kurt Lewin's Model, involved sixth-grade students in project-based learning. Before P5 implementation, the average critical thinking skill score of students was only 1.8, falling into the "sufficient" category (46.1%). Following Cycle I of P5, scores significantly increased to 2.8, reaching the "good" category (71.2%). The improvement continued in Cycle II, where the average score reached 3.7, placing it in the "very good" category (92.5%). This enhancement encompassed aspects like analyzing information, evaluating arguments, and problem-solving, demonstrating that P5 is highly effective in developing these skills in students.